The Islamic religious leaders as health promoters: improving maternal health in selected communities of Zamfara State, Nigeria - Maiwada, Abdullahi Mohammed; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; Ann-Walker, Judith (IDOSI Publications, 2016)
The project targeted Islamic religious leaders (ISOLs) through transformative interventions such as leadership development forums, health promotion and education training activities to the Islamic religious leader, who in return informed and educated their followership including men and women of reproductive age groups in order to help improve the maternal health situation and reduce maternal mortality in Zamfara states. Methods: a total of 100 Islamic religious leaders were engaged and exposed to health promotion and education trainings and community mobilization activities through the (IIUM/HPPMM) which was implemented in some selected intervention urban and rural communities of Zamfara State to women in reproductive age groups. Results revealed that there was an increase in some key output indicators such as antenatal care (ANC) attendance and contraceptive use among these women, delivery at the health facility also increased when compared with the control communities where no such interventions were carried out by the Islamic religious leaders and the project. The intervention rural facilities experienced an uptake in contraceptive use, ANC attendance and facility deliveries while the control sites saw no increase in uptake. Findings of particular significance in the rural facilities include the sharp increase in contraceptive use in the intervention compared to the control community facility. In the overall there is increase in ANC attendance in all the intervention rural and urban facilities compared to control sites. In conclusions: The findings of this analysis suggest that the (IIUM/HPPMM) Health Promotion and Prevention of Maternal Mortality Research and Leadership Development Project which assumes a health communication role for Islamic religious leaders has indeed contributed to the uptake of FP/RH services.